2018
DOI: 10.1634/theoncologist.2017-0546
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Radiotherapy in Invasive Vaginal Carcinoma: A Systematic Review

Abstract: Only retrospective studies, in a limited number, have been published on RT in VC in the past decade, with significant heterogeneity in terms of treatment characteristic and evaluation criteria. Clinical results were strongly influenced by tumor stage. Prospective randomized studies are needed to improve patients' outcomes, especially in advanced-stage disease.;23:1-10 IMPLICATIONS FOR PRACTICE: This study systematically reviews the recent literature on the role of definitive radiotherapy in the management of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, a significant portion of the population required adjuvant radiation therapy after surgery ( 34 ). Radiotherapy using external beam and/or brachytherapy is a standard treatment for vaginal cancer, especially in cases that are locally advanced ( 1 , 31 , 34 , 35 ). The principal advantage of radiation is organ preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a significant portion of the population required adjuvant radiation therapy after surgery ( 34 ). Radiotherapy using external beam and/or brachytherapy is a standard treatment for vaginal cancer, especially in cases that are locally advanced ( 1 , 31 , 34 , 35 ). The principal advantage of radiation is organ preservation.…”
Section: Discussionmentioning
confidence: 99%
“…The principal advantage of radiation is organ preservation. A systematic review conducted by Guerri et al reported that factors associated with better outcomes in the radiotherapy group included early stage of disease, small tumor size (<4 cm), previous hysterectomy, high pre-treatment hemoglobin levels and younger age (35). Another two retrospective studies demonstrated excellent outcomes with definitive radiotherapy, either with external-beam radiation therapy alone or in combination with brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity‐modulated radiation therapy can deliver high dosages of radiation to the cancer, and concurrent chemotherapy is thought to improve patient outcomes. Guerri et al reported five‐year overall survival rates of 35%‐78%, with severe late complication rates of 9%–23% for patients with SCC treated by radiotherapy 10 . Although no data from prospective trials are available, Miyamoto and Viswanathan reviewed retrospective studies and reported that chemoradiation therapy provided significantly better overall survival and disease‐free survival compared with radiation alone (respective three‐year overall survival rates of 79% versus 56% and three‐year disease‐free survival rates of 73% vs 43%) 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Guerri et al reported five-year overall survival rates of 35%-78%, with severe late complication rates of 9%-23% for patients with SCC treated by radiotherapy. 10 Although no data from prospective trials are available, Miyamoto and Viswanathan reviewed retrospective studies and reported that chemoradiation therapy provided significantly better overall survival and disease-free survival compared with radiation alone (respective threeyear overall survival rates of 79% versus 56% and threeyear disease-free survival rates of 73% vs 43%). 11 Nashiro et al claimed that chemoradiation therapy was effective for primary vaginal SCC and should be considered for patients with high-risk disease.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy (RT) represents a cornerstone in the treatment of gynecological tumors and, in cases of advanced cervical cancers, it is the only available therapy with curative intent [1][2][3][4][5][6]. However, some side effects affecting sexual function are well known.…”
Section: Introductionmentioning
confidence: 99%